The Effect of Exploitation Capacities on Organizational Performance: An Empirical Analysis (2017)
ABSTRACT: The effect of exploitation capacity (EC) vis-à-vis organizational performance (OP) has not been sufficiently studied and has low empirical evidence in developing countries such as Colombia. Absorption capacity based on exploitation capacity (EC) is considered to have been relevant for organizations in developing countries to significantly increase their performance via innovation. We examined the effect of exploitation capacity versus organizational performance using a sample of 227 companies located in Medellin, Colombia. The main findings indicate that companies can generate exploitation capacities in order to increase organizational performance, essentially seeking to combine information from different sources for their benefit, thereby directly contributing to the growth of benefits in the companies under study